Optimizing the Advantages of Monolingual Dictionary Utilization by Thai EFL Students - Jenpattarakul, Win (Richtmann Publishing, 2012)
The purposes of this research were to 1) investigate the use of dictionary of second-year students majoring in Englishat Bangkok University 2) compare the use of dictionary between the achievers and underachievers. The instruments used forcollecting data were a questionnaire and an in-depth interview. The population was 40 English major students from Humanitiesfaculty. The data were statistically analyzed in terms of mean and standard deviation. A t-test analysis was used to find thedifference between the achievers and underachievers on the use of dictionary. For the in-depth interview, six achievers and sixunderachievers are randomized through simple random sampling technique to give their opinions on three questions provided,and the data were collected to assure the results of the study. The results of this study showed that the overall usage ofdictionary of Bangkok University students was at a medium level, and significant differences existed in dictionary usage betweenthe achievers and underachievers. The findings of this research would let the teachers know the students’ problems andpurposes of using dictionary, so that the teachers can train the students to practice using dictionary systematically so as to makethe best use of dictionary. Pedagogical implications into reading comprehension and vocabulary acquisition were suggested.